Proses Pembuatan preform dengan material bahan polyethylene terephtalate menggunakan mesin injection molding - Fernanda Ramadhan, Ferdy (Universitas Majalengka, 2021)
Preform is a semi-finished material from a gallon product that is shaped like a chemical test tube, where the preform is made of polyethylene terephthalate (PET) material with the manufacturing process using an injection molding machine. Injection molding is a method of forming a thermoplastic material in which the material that melts due to heating is injected by a plunger into a mold that is cooled by water so that it hardens. In an injection molding machine, there is a screw base connected to the piston in a cylinder. This pressure is needed to inject the plastic material into the mold. To produce a good preform, you must check the preform injection molding machine and set its parameters. The combination of injection molding machine parameters, namely injection temperature 275-290⁰C, cavity filing time 70 seconds, clamping pressure 175 bar, coling time 50 seconds, holding time 2 minutes, and screw tip pressure pushing the material is 972.63 x pa.